A Novel 5-HT1B Receptor Agonist of Herbal Compounds and One of the Therapeutic Uses for Alzheimer’s Disease - Yang, Yang; Zhang, Lijing; Yu, Jiaojiao; Ma, Zhaobin; Li, Moxiang; Wang, Jin; Hu, Pengcheng; Zou, Jia; Liu, Xueying; Liu, Ying; An, Su; Xiang, Cheng; et al. (Frontiers in Pharmacology, 2021)
The serotonin receptor 5-HT1B is widely expressed in the central nervous system and has been considered a drug target in a variety of cognitive and psychiatric disorders. The anti-inflammatory effects of 5-HT1B agonists may present a promising approach for Alzheimer’s disease (AD) treatment. Herbal antidepressants used in the treatment of AD have shown functional overlap between the active compounds and 5-HT1B stimulation. Therefore, compounds in these medicinal plants that target and stimulate 5-HT1B deserve careful study. Molecular docking, drug affinity responsive target stability, cellular thermal shift assay, fluorescence resonance energy transfer (FRET), and extracellular regulated protein kinases (ERK) 1/2 phosphorylation tests were used to identify emodin-8-O-β-D-glucopyranoside (EG), a compound from Chinese medicinal plants with cognitive deficit attenuating and antidepressant effects, as an agonist of 5-HT1B. EG selectively targeted 5-HT1B and activated the 5-HT1B-induced signaling pathway. The activated 5-HT1B pathway suppressed tumor necrosis factor (TNF)-α levels, thereby protecting neural cells against beta-amyloid (Aβ)-induced death. Moreover, the agonist activity of EG towards 5-HT1B, in FRET and ERK1/2 phosphorylation, was antagonized by SB 224289, a 5-HT1B antagonist. In addition, EG relieved AD symptoms in transgenic worm models. These results suggested that 5-HT1B activation by EG positively affected Aβ-related inflammatory process regulation and neural death resistance, which were reversed by antagonist SB 224289. The active compounds such as EG might act as potential therapeutic agents through targeting and stimulating 5-HT1B for AD and other serotonin-related disorders. This study describes methods for identification of 5-HT1B agonists from herbal compounds and for evaluating agonists with biological functions, providing preliminary information on medicinal herbal pharmacology.